LGG-41. The clinical and molecular landscape of gliomas in adolescents and young adults. (3rd June 2022) - Bennett, Julie; Nobre, Liana; Sheth, Javal; Ryall, Scott; Fang, Karen; Johnson, Monique; Negm, Logine; Chung, Jiil; Komosa, Martin; Nunes, Nuno M; Fat, Mary Jane Lim; Perry, James; et al.
Abstract: OBJECTIVE: Gliomas in adolescents and young adults (AYA) are commonly treated with a standard chemo-radiation approach based on data from adults. The clinical impact of paediatric-type alterations in these tumours is unknown. METHODS: We compiled a multi-institutional cohort of patients diagnosed with glioma between 15-39.9 years over 20 years. Complete molecular analysis, therapeutic data and outcome was collected. For specific alterations, analysis included patients aged 0-39.9 years. RESULTS: A total of 1900 patients with 876 AYA gliomas were included. Ongoing analysis reveals genetic alterations in 95% of available tumours. IDH-mutant tumours account for only 53%, while paediatric-type mutations were found in 35% of AYA tumours with IDH-WT GBM accounting for the remaining 12%. The most common paediatric alterations in AYAs included BRAF p.V600E (11%) and FGFR alterations (6%) while BRAF fusions, H3 p.K27M and H3.3 p.G34R were rarely observed (4%, 4% and 1% respectively). BRAF fused tumours with non-canonical binding partners were enriched in AYAs. Analysis of BRAF-V600E gliomas between ages 0-40 revealed increased tendency for malignant tumours in patients >20 years suggesting malignant transformation possibly due to higher rate of secondary hits including TP53, CDKN2A and ATRX mutations. This resulted in worse overall-survival for AYA patients with BRAF-V600E glioma when compared to children under 20 years (p=0.0032). Ten-year OS of 100%, 90% and 95% was seen for BRAF fused, BRAF-V600E and FGFR-altered AYA low grade glioma respectively, compared to 14% and 25% for BRAF-V600E and FGFR-altered high grade glioma. In contrast, continuous decline was observed in the IDH-mutant gliomas with 10-year OS of 50% which declined to 29% at 15 years. CONCLUSIONS: Gliomas in AYA are enriched for paediatric-type alterations with distinct molecularly-based outcomes. As these tumours carry different outcomes than childhood glioma and may respond to targeted inhibitors, AYA gliomas would benefit from comprehensive diagnostic and therapeutic approaches.